Decision-making practice in youth soccer: A cross-comparison of coaching contexts from top-division professional clubs in England, Germany, Portugal and Spain - Roca, A.; Ford, P. R. (2020)
A key performance attribute that discriminates highly-skilled soccer players from their lesser-skilled counterparts is the ability to anticipate and make effective decisions under pressure during match play (e.g., [1]). Researchers have shown that these `game intelligence` skills are primarily acquired through activities in which practice has the same underlying structure as competition (e.g., [2]). The aim of this study was to investigate the structures of practice activities used by youth soccer coaches working in the youth academies of professional topdivision clubs from England, Germany, Portugal, and Spain. This was the first study to assess the microstructure of coach-led practice in youth soccer across multiple countries. METHODS: Altogether, 53 male soccer coaches working with under- 12 to under-16 age group male players across 16 youth academies of professional top-division clubs in four European nations took part. A total of 83 practice sessions were analysed in situ. Sessions were analysed for the proportion of time in `non-active decision-making` (e.g., unopposed technical or tactical skills practices, fitness training) and `active decision-making` activities (e.g., small-sided games, skills practice with opposition), with the latter deemed superior for the transfer of `game intelligence` skills to match play. RESULTS: More time was spent in active decision-making (M = 62%) compared to non-active decision-making activities (M = 20%) and transitioning between activities (M = 17%). Players from Portugal and Spain spent a higher amount of time in active decision-making activities compared to English and German players. English players spent more time in unopposed technical-based drills and German players in improving fitness aspects of the game without the ball. CONCLUSION: Our findings extend previous research assessing coach-led youth soccer practice in single countries by demonstrating differences in specific training activities and environments between youth academies at professional clubs in multiple European countries.